Perbandingan Dua Teknik Modifikasi Aromaterapi Lavender sebagai Terapi Komplementer pada Nyeri Persalinan Kala I Fase Aktif - Dini Rahmania; Yanti Cahyanti; Santi Yuliastuti; Dede Gantini; Uly Artha Silalahi; Abil Rudi (STIKes Persada Husada Indonesia, 2026)
Research Objective: This study aimed to determine the effect of modified lavender aromatherapy on labor pain among women in the active phase of the first stage of labor at the PONED Room of UPTD Karangnunggal Public Health Center, Tasikmalaya Regency, in 2026. Methodology: This study used a quantitative quasi-experimental design with a two-group pretest-posttest approach. The sample consisted of 50 primiparous women divided into two intervention groups: inhalation–massage lavender aromatherapy and inhalation–warm compress lavender aromatherapy. Pain intensity was measured before and after the intervention using the Numerical Rating Scale (NRS). Data were analyzed using univariate and bivariate statistical tests. Results: The results showed a decrease in labor pain intensity after both interventions. Both the inhalation–massage lavender aromatherapy group and the inhalation–warm compress lavender aromatherapy group demonstrated significant differences between pretest and posttest pain scores. Lavender aromatherapy provided relaxation effects and reduced pain perception through stimulation of the limbic system and gate control mechanisms. Conclusion: Modified lavender aromatherapy is effective in reducing labor pain during the active phase of the first stage of labor. Both intervention methods may be used as complementary non-pharmacological approaches in midwifery care to improve maternal comfort during labor.